PERAN APARAT PEMERINTAH DALAM PELAYANAN ADMINISTRASI YANG EFEKTIF DI KECAMATAN KABILA KABUPATEN BONE BOLANGO - Tri Susanti Lamangida (Publik : (Jurnal Ilmu Administrasi), 2015)
This research aims to find out how the role of government officials in giving the effective of administrative services in sub-district of Kabila Bone Bolango regency. The method of this research is descriptive qualitative. This research is is a qualitative descriptive research that conducted on independent variables, that is without making comparisons or connect with other variables. The research shows still low capacity of government officials in both of sub-district Kabila in giving the excellent service to the society and to the achievement of an effective and efficient work. The society awareness work together is potentially a very noble and honorable, so there has a willingness of the society to develop their regions. Suggested to local governments, need greater attention to the good service for society. To remember low awareness of government officials in sub-district of Kabila, it is expected that the attention of the regency government in this case government of Bone Bolango, to give education and training, to give training for government officers that spread throughout the all regency, that will produce the quality of resources to face the application of the principles of Good Governance.